Improvement Of Ex-Gold Mining Soil Through The Application Of Rubber Leaf Litter Compost And Biochar Of Oil Palm Empty Fruit Bunches On The Growth Of Rubber Seedlings (Hevea Brasiliensis Muell. Arg.) Pb-260 Clone - Widia Febriana; Gusmini; Yulistriani (Jurusan Budidaya Perkebunan, 2023)
Land damage caused by gold mining activities is mainly due to soil contamination by Mercury (Hg). Ex-gold mines are soils that have poor chemical, biological, and physical properties, resulting in a very low level of soil fertility. The objective of this study was to determine the effect of rubber leaf litter compost and biochar of oil palm empty fruit bunches to obtain the best dose recommendation in improving the ex-gold mining soil on the growth of rubber seedlings (Hevea brasiliensis Muell. Arg.). This study was designed by a completely randomized design consisted of 7 treatments and repeated 3 times. The treatments were rubber leaf litter compost at a dose of 10 tons/ha and 20 tons/ha, biochar of oil palm empty fruit bunches at a dose of 10 tons/ha and 20 tons/ha, combination of rubber leaf litter compost and biochar of oil palm empty fruit bunches at a dose of 10 tons/ha and 20 tons/ha, respectively. The results showed that the combination treatment of rubber leaf litter compost and biochar of oil palm empty fruit bunches at a dose of 20 tons/ha resulted in a soil pH value of 4,85, Al-dd 0,42 cmol/kg, C-organik 0,92%, N-total 0,053%, C/N 11,25, P-available 122,69 ppm, K-dd 0,40 cmol/kg, and reducing soil mercury by 0,01 ppm. The growth of shoot height and leaves number of rubber seedlings was obtained by the application of biochar of oil palm empty fruit bunches at a best dose of 20 tons/ha. In addition, the treatment of rubber leaf litter compost at a dose of 20 tons/ha was able to increase the leaf width of rubber seedlings (h. brasiliensis Muell. Arg.).